Territorial and Programmatic Eccentricity: Three Public Art Programs in Portugal - Castro, Laura Oliveira (Farol, 2025)
This article presents three public art programs implemented in Portugal since 2018, located in small towns and rural areas. These are the "Poldra" programs in the city of Viseu, "Desencaminharte" in the Alto Minho region, and "Experimenta Paisagem" in central Portugal. These programs highlight a trend in public art over recent decades and a lineage of international cases, marked by the search for eccentric territories and an approach to the non-urban landscape. Also noteworthy is the connection between these practices and regional and tourism development objectives, as well as a commitment to sustainability, which confirms the multiplicity of actors involved and the social instrumentalization of art in an attempt to meet the interests and needs of the population.
Keywords: public art; landscape; rural territory; contemporary art